The mechanism of empowering the Da’i role in Da’wah bil hal using surah Al-Taubah - Abdul Razak, Azizul Azra; Abdul Rahim, Mohd. Hisyam (American Journal of Humanities and Social Sciences Research, 2019)
Da‟wah consists of important activities to invite the community members to do good and to avoid negative things. Da‟wah activties can be conducted via da‟wah bil lisan and da‟wah bil hal. However, this study would only look at the activities of da‟wah bil hal, analysing the features of da‟i bil hal and developing a mechanismfor empowering the da‟i in da‟wah bil hal based on surah al-Taubah. This study utilised the qualitative method with the study design focusing on the document analysis of 50 verses from surah al-Taubah which had been analysed using thematic analysis. The findings identified 3 main aspects representing 25 verses which fit the aspects of approach, action (20 verses) and target (10 verses). Therefore, the role of da‟i in da‟wah bil hal could be improved using the comprehensive mechanism framework. The study implications showed that da‟wah bil hal was a da‟wah method equally important as da‟wah bil lisan and it should be a good alternative in the current da‟wah context. As such, this framework of da‟wah bil hal da‟i empowerment would be helpful to improve current efforts in da‟wah.